Customers' savings rate and share of wallet: the moderating role of religion and ethnicity/immigrant generation vis-à-vis attitude as mediator. (4th July 2018) - Hamin, Hamin; Tung, Rosalie L.; Baumann, Chris; Hoadley, Susan
Abstract: This study explores the role of attitude toward money, religion and ethnicity in the relationship between income and consumer behavior. The three-country (Australia, Canada and China) study sampled 755 consumers and uses structural equation modeling and multivariate analysis to test for mediating effects of attitude toward money and moderating effects of religion and ethnicity/immigrant generation. Religion is found to be a moderating variable for savings rate and share of wallet, while ethnicity/immigrant generation only moderates the association between income and savings rate. We also demonstrate the interaction effects of religion and ethnicity/immigrant generation with income as determinants of savings rate and share of wallet. This research provides the foundation for modeling savings rate and share of wallet, incorporating attitude, religion, and ethnicity/immigrant generation, as well as income, demonstrating the need to include other factors (i.e. demographic factors in addition to attitudinal/satisfaction measures) to better identify, understand and strategically target consumer segments with potential for profitability and growth.